Occupational health and safety start at school of engineering. Issue 1 (October 2021) - Ramirez, M; Pastor, A; Diaz, E; Piñero, D; Batista, M
Abstract: The occupational risk prevention has been the subject of study for many years, but it could be said that in Spain, it is from the promulgation of laws in this regard when it becomes more important in view of the need to reduce the accident rate in all professions. Focusing on the engineering profession, the need arises to know if in their training stages, this matter is contemplated by developing a preventive culture in the person that helps to become familiar with and minimize risks. That is why this study aims to find out how this subject is dealt with in Spanish universities. To this end, it proposes the study through the Spanish universities best positioned in international rankings such as the Academic Ranking of World Universities (ARWU) and Quacquarelli Symonds, known as QS World University Ranking. The results of the study show that Spanish universities are not very well disposed towards this subject, thus depriving future engineers of the acquisition of competencies related to risk prevention.